Evaluation of the Effects on Uninfected Pregnant Women and Their Pregnancy Outcomes During the COVID-19 Pandemic in Beijing, China - Hao, Chongyi; Jin, Feng; Hao, Chanjuan; Zhang, Xiaofen; Xie, Limin; Zhang, Yawei; Liu, Xuanshi; Ni, Xin; Li, Wei (Frontiers in Medicine, 2022)
Background People's lifestyles may have changed during the COVID-19 pandemic, which may have a profound impact on pregnant women and newborns. This study aims to assess the effects of the COVID-19 pandemic on uninfected pregnant women and their newborns, including potential environmental factors. Methods We retrospectively analyzed the pregnancy complications of 802 cases in the pandemic group and 802 controls in the pre-pandemic group in a matched nested case-control study, and evaluated the association with sociodemographic features, lifestyles, and other factors in 311 pregnant women with adverse pregnancy outcomes. Results Compared to the pre-pandemic group, the rates of anemia, vaginitis, shoulder dystocia, and adverse pregnancy outcomes such as preterm birth were increased in the pandemic group. After controlling for the covariates, we observed a higher risk of adverse pregnancy outcomes in the pandemic group. Pregnant women with adverse pregnancy outcomes had an increased rate of anemia and vaginal candidiasis. Conclusion COVID-19 pandemic has profound effects on adverse pregnancy outcomes, suggesting the importance of ensuring regular prenatal checkups and keeping a healthy lifestyle.